If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 32 = 122 Reorder the terms: 32 + 6x = 122 Solving 32 + 6x = 122 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-32' to each side of the equation. 32 + -32 + 6x = 122 + -32 Combine like terms: 32 + -32 = 0 0 + 6x = 122 + -32 6x = 122 + -32 Combine like terms: 122 + -32 = 90 6x = 90 Divide each side by '6'. x = 15 Simplifying x = 15
| -11(26x-52)=44(-9x+3) | | 6p*3= | | 48/3=x/4 | | 5+3(-2)=-1 | | 30+0.35c=72 | | 3s=3 | | 2.5z=-75 | | 5(2)+3(0)=-1 | | -10t=-8t+10 | | 2.8=2n-5 | | W+3.34=5.64 | | 3x+(k+2)x=1-k | | -9+4d=9+2d | | 16-6(n)=2+n | | 4.8-1.8=0.4y | | -5*-25=25-10*-25 | | 4n^2-35=-4n | | y=43+-10x | | Y-6.8=7.4 | | -4b+4=2 | | y=-10x+43 | | 2x-11=7x+44 | | 83+(-9)=92 | | 10r=5+9r | | 12x^3/18x^6 | | -6y+33=-9(y-5) | | 7h=6h+3 | | 25+0.25p=60 | | X+2y=471 | | 4x-9y+x-5y+2= | | 13(n-2)=-4(11+m)+1 | | 2(y+8)=5y+28 |